Visible light photoredox mediated C-C bond formation under metal-free condition - Das, Mrinmoy (Nanyang Technological University, 2020)
Over the last decade, visible-light photoredox catalysis is rising as an important route for new chemical bond formation. The source of activation is visible-light which helps the reaction to occur in ambient temperature. In addition, due to the ability to tune the redox potential of other molecule, photoredox catalyst enables several challenging transformations easier. As a consequence, photoredox catalysts can facilitate many unfavourable electron transfer processes by diminishing the earlier reports and proceed the reaction through different pathways. Because of its usefulness towards organic synthesis the reports using this strategy is increasing gradually. Therefore, I intended to develop novel C-H activation strategies during my doctoral research work by employing organo-photoredox catalysis. The first chapter of this thesis describes photoredox catalysis, photophysical properties and application towards organic chemistry. Subsequently, in the second chapter we have developed a metal-free C-C bond forming method which involves C-H activation of phosphonium ylides, followed by the addition of electron rich olefin. This work describes a novel strategy to generate carbyne equivalents from phosphonium ylides under photoredox condition. Finally, in the last chapter we have successfully introduced photocatalytic metal free method for the intermolecular radical-radical cross coupling involving ketyl radical to produce complex tertiary alcohols.